Scanning electron microscopic study on the structure of the lingual papillae of the karacabey merino sheep - Mehmet Can; Şükrü Hakan Atalgın; Sevinç Ateş; Lütfi Takçı (Eurasian Journal of Veterinary Sciences)
Aim: It was aimed to determine the scanning electron misroscopic structures of the lingual papillae in Karacabey Merino Sheep in this study. Materials and Methods: Ten male young Karacabey Merino Sheeps were used. Tissues were received from the dorsal, ventral and ventro-lateral surfaces of the apex, body and root of of the tongue. Tissues were examined by scanning elecron microcopy (SEM). Results: Filiform, lentiform and conical papillae were observed three types as mechanical papillae and fungiform and vallate papillae were observed two types as gustatory papillae on the tongue in Karacabey Merino Sheep. The filiform papillae were present on the apex and body of the tongue, in addition randomly determined lateral surface of the apex. The conical papillae were round base and had a blunt tip and these papillae differed from the filiform papillae with their larger size and absence of the secondary papillae. The fungiform papillae round in shape and mushroom-like, scattering among the filiform papillae on the dorsal surface of the apex, body and the root of the tongue. The lentiform papillae were determined in two types. While the pyramidal-shaped type I lentiform papilla had a pointed apex, the round-shaped type II lentiform papilla had a blunt apex. The vallate papillae were defined bud ditch and a thick annular pad. Conclusions: It was determined that Karacabey Merino sheep linguae were equiped with lots of papillae with different morphologic features. Lingual papillae of Karacabey Merino sheep had mechanical function which similar to Jamunapari goat, Saanen Goat, sheep.